2012
DOI: 10.5539/ibr.v5n11p95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Professional Ethics on Development of Intellectual Capital at Agriculture Bank

Abstract: The present study aims at evaluating effects of observing professional ethics on development of intellectual capital at Agriculture Bank of West Azerbaijan province (Iran). For this purpose, professional ethics and intellectual capital have been defined in accordance with ethical charter of Bank Agriculture Bank and Bontis theory, respectively. Statistical population of the study was consisted of 449 personnel of the mentioned bank selected relying on classified random sampling method. Volume of statistical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In another study conducted in Iran, Beikzad, Abdolapoor et al (2012) found that professional ethics have a significant impact on intellectual capital and its dimensions, including human, structural and relationship capitals. These capitals are key resources for commercial development of companies and help to create competitive advantages.…”
Section: Professional Ethics and Its Role In Business Performancementioning
confidence: 97%
See 1 more Smart Citation
“…In another study conducted in Iran, Beikzad, Abdolapoor et al (2012) found that professional ethics have a significant impact on intellectual capital and its dimensions, including human, structural and relationship capitals. These capitals are key resources for commercial development of companies and help to create competitive advantages.…”
Section: Professional Ethics and Its Role In Business Performancementioning
confidence: 97%
“…Therefore, whether society and its members can get benefits from professionals, depends on the way professionals practice their professional actions [7,15]. In other words, professional ethics can be seen as individual ethical responsibility from an occupational perspective [4].…”
Section: Introduction mentioning
confidence: 99%